Development of Molecular Markers for Iron Metabolism Related Genes in Lentil and Their Expression Analysis under Excess Iron Stress - Sen Gupta, Debjyoti; McPhee, Kevin; Kumar, Shiv (Frontiers in Plant Science, 2017)
Iron uptake and translocation in plants from soil is regulated by multiple genes and transcription factors. This study was designed to develop iron metabolism related molecular markers for Ferritin-1, BHLH-1 (Basic helix loop helix) or FER-like transcription factor protein and IRT-1 (Iron related transporter) genes using genome synteny with barrel medic (Medicago truncatula) to facilitate allele mining for these genes in lentil germplasms. The another objective of this study was to analyze differential gene expression under excess iron over time (2h, 8h, 24h). Specific molecular markers were developed for iron metabolism related genes (Ferritin-1, BHLH-1, IRT-1) and validated in lentil. Gene specific markers for Ferritin-1 and IRT-1 were used for quantitative PCR (qPCR) studies based on their amplification efficiency. Significant differential expression of Ferritin-1 and IRT-1 was observed under excess iron conditions. Future studies should involve field conditions under external iron supply.